2008
DOI: 10.1128/mcb.00331-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ABCG2 Expression at the 3′ Untranslated Region of Its mRNA through Modulation of Transcript Stability and Protein Translation by a Putative MicroRNA in the S1 Colon Cancer Cell Line

Abstract: ABCG2 is recognized as an important efflux transporter in clinical pharmacology and is potentially important in resistance to chemotherapeutic drugs. To identify epigenetic mechanisms regulating ABCG2 mRNA expression at its 3 untranslated region (3UTR), we performed 3 rapid amplification of cDNA ends with the S1 parental colon cancer cell line and its drug-resistant ABCG2-overexpressing counterpart. We found that the 3UTR is >1,500 bp longer in parental cells and, using the miRBase TARGETs database, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 51 publications
(62 reference statements)
5
146
0
Order By: Relevance
“…Recent studies have shown that other proteins involved in drug metabolism (Tsuchiya et al, 2006;Takagi et al, 2008;To et al, 2008;Pan et al, 2009) are also subject to miRNA regulation. Our results, taken together with those findings, suggest a complex regulatory mechanism for cytochromes P450 by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that other proteins involved in drug metabolism (Tsuchiya et al, 2006;Takagi et al, 2008;To et al, 2008;Pan et al, 2009) are also subject to miRNA regulation. Our results, taken together with those findings, suggest a complex regulatory mechanism for cytochromes P450 by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Kenneth et al 58 have shown that ABCG2 mRNA adopts a longer 3 0 UTR in the parental S1 colon cancer cell line than its mitoxantrone-resistant counterpart S1MI80. HsamiR-519c decreases ABCG2 mRNA and protein levels by acting through a putative binding site located within the longer 3 0 UTR in parental cells, but the binding site for this miRNA is lost in the shorter 3 0 UTR in the resistant cells, therefore mRNA degradation and/or repression on protein translation is relieved, which contributes to the overexpression of ABCG2.…”
Section: Colon Cancermentioning
confidence: 99%
“…They usually act through base pairing to a partially complementary segment within the 3ЈUTR transcript of a target gene, which causes translation inhibition and/or mRNA cleavage and leads to a reduced expression of the target gene. With the understanding of miRNA function, there is increased interest in delineating the role of miRNAs in posttranscriptional regulation of drug-metabolizing enzymes, drug transporters, and nuclear receptors (Tsuchiya et al, 2006;Yu, 2007;Kovalchuk et al, 2008;Liao et al, 2008;Takagi et al, 2008;To et al, 2008;Zhu et al, 2008;Ji et al, 2009;Pan et al, 2009), which may not only provide insight into miRNA biological function but also advance the understanding of the integrated response of cells to xenobiotic drugs. Of note, Takagi et al (2008) has shown that CYP3A4 can be indirectly regulated by miRNA via microRNA-148a (miR-148a)-controlled regulation of PXR.…”
mentioning
confidence: 99%